PENGARUH PENGEMBANGAN SUMBER DAYA MANUSIA DAN MOTIVASI TERHADAP KINERJA PEGAWAI DINAS PARIWISATA KOTA BATU - bayu krisdianto; Nurhajati Nurhajati (Jurnal Ilmu Manajemen (JIMMU), 2020)
The purpose of this study is to measure and analyze whether there is influence of human resource development and motivation on the performance of existing employees in the Tourism Department of Batu City.The population used in this study is all employees who are in the environment of the Department of Tourism City of Batu by using the census method is to take all existing employees as respondents. This research uses descriptive method of analysis and verification with qualitative approach, and using multiple linear regression analysis. In this research it can be seen that the development of human resources partially and significantly affect the performance of existing employees in Batu City Tourism Department with obtained tcount 2.131 and p-value 0.037 <0.05 and human motivation partially and significantly affect the performance Employees who exist in Batu City Tourism Department with obtained tcount 2,311 and p-value 0,024 <0,05. While the results of the test f obtained F-count = 4.494 and the value of p-value = 0.015 <0.05 which means the development of human resources and motivation simultaneously affect the performance of employees in Batu City Tourism Department. Keywords: human resource development, motivation and performance.